Статичне моделювання випробування радіоелектронної апаратури на надійність - Зіад Карім Халіль Мохамед (ХНУРЕ, 2024)
The article discusses a program developed for simulating the reliability of radio-electronic equipment. It uses various mathematical modeling methods to study system reliability, focusing on specific system variants. The program, based on a database of failure intensity data, allows for testing and evaluating reliability parameters under different conditions. It's beneficial for students working on projects and for conducting scientific research
Keywords: випробування на надійність